Intraocular pressure during cardiopulmonary bypass. Issue 3 (March 1987) - Larkin, D F; Connolly, P; Magner, J B; Wood, A E; Eustace, P
Abstract : Intraocular pressure was measured in 24 patients undergoing elective cardiopulmonary bypass surgery. There was a rapid rise when the bypass circulation began, and this was maintained for about 30 minutes. A simultaneous drop in arterial perfusion pressure and packed cell volume occurred. We suggest that marked haemodilution is responsible for this effect, through increased ocular blood flow and low colloidal osmotic pressure. The possible aetiological significance in relation to ischaemic optic neuropathy complicating cardiopulmonary bypass is discussed.